2005
DOI: 10.1074/jbc.m500620200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of c-Fos by Members of the p38 MAPK Family

Abstract: Exposure to sources of UV radiation, such as sunlight, induces a number of cellular alterations that are highly dependent on its ability to affect gene expression. Among them, the rapid activation of genes coding for two subfamilies of proto-oncoproteins, Fos and Jun, which constitute the AP-1 transcription factor, plays a key role in the subsequent regulation of expression of genes involved in DNA repair, cell proliferation, cell cycle arrest, death by apoptosis, and tissue and extracellular matrix remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 63 publications
4
143
0
Order By: Relevance
“…Thus, GSK-3b appears to be an arbiter of cell fate towards proliferation, arrest or apoptosis. Further, it would also be interesting to investigate the role of P38 in stress signaling already known to induce c-Fos phosphorylation and gene trans-activation following UV stress [30] and to characterize the molecules that facilitate cross-talk between checkpoint kinases and mitogenic signaling under genotoxic stress. In fact a recent report suggests that ATR can transiently activate GSK-3b following UV irradiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GSK-3b appears to be an arbiter of cell fate towards proliferation, arrest or apoptosis. Further, it would also be interesting to investigate the role of P38 in stress signaling already known to induce c-Fos phosphorylation and gene trans-activation following UV stress [30] and to characterize the molecules that facilitate cross-talk between checkpoint kinases and mitogenic signaling under genotoxic stress. In fact a recent report suggests that ATR can transiently activate GSK-3b following UV irradiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of XT-I promoter by p38 signaling pathways is probably due to phosphorylation of c-Fos by p38 MAPKs. Indeed, it has been shown that p38 MAPKs are able to activate c-Fos (42,43). Thus, this pathway acts concomitantly with the activation of c-Jun by JNK/MAPK, thereby contributing to the complexity of AP-1 driven XT-I gene transcription regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Coincidently, vGPCR-induced p38␣ phosphorylates and induces the transcriptional activity of Hif-1␣, a hypoxia-inducible factor that regulates the expression of the vegf promoter (40). In addition, p38␣ regulates AP-1 transcriptional activity (61), and this transcription factor also controls vGPCR-driven vegf promoter activity (15,24). Interestingly, very recent studies have shown that STAT3 is required by vGPCR to induce transformation (62) and by several other oncogenes to induce VEGF secretion (63).…”
Section: Discussionmentioning
confidence: 99%